Monitoramento da contribuição de equipes de desenvolvimento na evolução de itens da dívida técnica em projetos de software Salvador - SANTOS, Sandro Luiz Abreu Campos dos (2018)
The software development environment is surrounded by challenges. In addition to short deadlines and restricted budgets, different levels of developer knowledge and experience are contributing factors to poor quality in the software maintenance process. Through decisions made consciously or accidentally, the lack of good practices favors the emergence of Technical Debt (TD). The process of identifying and monitoring DT's presence is as important as investigating those involved in the emergence, in an attempt to understand the main causes and reduce negative impacts. This work relates knowledge about DT and developers with the objective of identify and monitoring how those involved in the software development process contribute to the evolution of DT present in the project source code. In this context, this paper proposes a strategy for monitoring DT's evolution and how the developers contributed to it. It also presents the VisminerTD tool, which has many functionalities to support the application of the strategy. As an evaluation of the strategy, a case study was elaborated and executed. The results pointed to positive evidence regarding the use of the proposed strategy to monitoring the evolution of the DT, being able to substantiate the need to qualify or relocate the people involved in the software development process, in order to avoid future problems